V. I. Surikov House-Museum: Mycological investigation - Zvonareva, Polina (project baikal, 2025)
The investigation of the Surikov House-Museum, a cultural heritage site of federal significance, was conducted in order to develop technical specifications for chemical protection of the building against biodegradation. During the investigation, samples were taken from the external load-bearing walls, where damage caused by various biodegraders was found. Analysis of the samples showed the presence of microorganisms that contribute to the degradation of building materials. The article emphasises the importance of the correct choice of means of protection to ensure the durability of the architectural monument and offers recommendations to eliminate the identified problems.